(untitled) (Upper Saddle River, N.J., 2003)
The field of distance learning is growing in importance and size. This introductory distance education textbook gives readers the basic information they need to be knowledgeable distance educators. Understanding that most students would prefer to sit in a classroom, the book offers practical solutions for providing equivalent opportunities for various ways of learning. Distance education requires considerable pre-planning in order to be effective, and yet when designed and delivered correctly, it allows the teacher to move beyond the simple delivery of content to the guiding of the learning process. This book is the most comprehensive and widely adopted for distance learning courses and also provides the most visuals. It fills the need for a research-based book about the best practices in distance education.
Keywords: Distance education